Evolution of Plant Architecture in Oryza Driven by the PROG1 Locus - Huang, Liyu; Liu, Hui; Wu, Junjie; Zhao, Ruoping; Li, Yanxia; Melaku, Getachew; Zhang, Shilai; Huang, Guangfu; Bao, Yachong; Ning, Min; Chen, Benjia; Gong, Yurui; et al. (Frontiers in Plant Science, 2020)
The genetic control of plant architecture in crops is critical for agriculture and understanding morphological evolution. This study showed that an open reading frame (ORF) of the rice domestication gene PROG1 appeared 3.4–3.9 million years ago (Mya). Subsequently, it acquired a novel protein-coding gene function in the genome of O. rufipogon ( 0.3–0.4 Mya). This extremely young gene and its paralogous C2H2 genes located nearby define the prostrate architecture of O. rufipogon and, thus, are of adaptive significance for wild rice in swamp and water areas. However, selection for dense planting and high yield during rice domestication silenced the PROG1 gene and caused the loss of the RPAD locus containing functional C2H2 paralogs; hence, domesticated lines exhibit an erect plant architecture. Analysis of the stepwise origination process of PROG1 and its evolutionary genetics revealed that this zinc-finger coding gene may have rapidly evolved under positive selection and promoted the transition from non- or semi-prostrate growth to prostrate growth. A transgenic assay showed that PROG1 from O. rufipogon exerts a stronger function compared with PROG1 sequences from other Oryza species. However, the analysis of the expression levels of PROG1 in different Oryza species suggests that the transcriptional regulation of PROG1 has played an important role in its evolution. This study provides the first strong case showing how a fundamental morphological trait evolved in Oryza species driven by a gene locus.